Extraction of heat-stable enterotoxin of Yersinia enterocolitica - Nawal Aziz Khalil; Ameera Mahmood Alrawi (College of Education for Pure Sciences, 2013)
ABSTRACT Extraction of heat-stable enterotoxin of Yersinia enterocolitica and dosage suckling mice with toxin were done, then sections to study histological changes for some animal organs were prepared. Histopathological changes and necrosis were reported in intestine, liver and lungs of mouse after injection with heat-stable enterotoxin.